Analysis of Battery/Generator Hybrid Container Ship for CO2 Reduction - Kyunghwa Kim; Kido Park; Jaehoon Lee; Kangwoo Chun; Seok-Hyun Lee (IEEE Access, 2018)
Ships entering designated emission control areas are required to reduce emission gases drastically, in accordance with international maritime organization regulations or local policies. In this regard, a hybrid power system, which is a combination of conventional generators and lithium-ion batteries as a type of energy storage system (ESS), has been applied to ships. However, this hybrid concept has been focused on small-sized coastal ships, because they have a short voyage time or require high peak power for a short time. And by extension, this paper demonstrates the potential of a hybrid power system for mediumsized oceangoing ships. First, a medium-sized container ship is selected as a target ship. The electric load profile near ports is defined to select the optimum capacity of the ESS and generators. Then, to verify the advantage of the proposed system, this paper uses MATLAB/Simulink software for simulation. Finally, carbon dioxide (CO2) emissions are compared between the proposed power system and the conventional one which uses only generators. The results show that overall, 8.6% ~ 20.7% CO2 emissions can be reduced, depending on the electric load conditions of a ship. Hence, a hybrid power system can be an eco-friendly solution for medium-sized oceangoing ships, as well as small-sized coastal ships.